Political economy of renewable resource federalism. Issue 3 (16th February 2021) - Sanchirico, James N.; Blackwood, Julie C.; Fitzpatrick, Ben; Kling, David M.; Lenhart, Suzanne; Neubert, Michael G.; Shea, Katriona; Sims, Charles B.; Springborn, Michael R.
Abstract: The authority to manage natural capital often follows political boundaries rather than ecological. This mismatch can lead to unsustainable outcomes, as spillovers from one management area to the next may create adverse incentives for local decision making, even within a single country. At the same time, one‐size‐fits‐all approaches of federal (centralized) authority can fail to respond to state (decentralized) heterogeneity and can result in inefficient economic or detrimental ecological outcomes. Here we utilize a spatially explicit coupled natural–human system model of a fishery to illuminate trade‐offs posed by the choice between federal vs. state control of renewable resources. We solve for the dynamics of fishing effort and fish stocks that result from different approaches to federal management that vary in terms of flexibility. Adapting numerical methods from engineering, we also solve for the open‐loop Nash equilibrium characterizing state management outcomes, where each state anticipates and responds to the choices of the others. We consider traditional federalism questions (state vs. federal management) as well as more contemporary questions about the economic and ecological impacts of shifting regulatory authority from one level to another. The key mechanisms behind the trade‐offs include whether differences in local conditions are driven by biological or economic mechanisms; degree of flexibility embedded in the federal management; the spatial and temporal distribution of economic returns across states; and the status‐quo management type. While simple rules‐of‐thumb are elusive, our analysis reveals the complex political economy dimensions of renewable resource federalism.